F1 racing confidential : inside stories from the world of Formula One - Richards, Giles (Grand Central, 2024)
"An access-all-areas look inside the thrilling world of Formula One. Formula One is one of the most intense, complex and secretive sports on the planet. Recent documentaries such as Netflix's Drive to Survive series have given a glimpse of life inside the paddock, but there are so many more stories from this high-stakes, globetrotting world that remain untold. In F1 Racing Confidential, Guardian journalist Giles Richards draws on more than a decade of experience working at the heart of Formula One to reveal the inner workings of the world's most glamorous motorsport. Featuring exclusive interviews with men and women working at every level of F1 Teams including Mercedes, Red Bull, Ferrari, McLaren, Alfa Romeo, and Aston Martin, this is an unprecedented, behind-the-scenes look at the complete workings of a modern Formula One team. With contributions from high-profile insiders, including Christian Horner, Lando Norris, and Toto Wolff, each with their own fascinating stories, insights and revelations, F1 Racing Confidential pulls back the curtain on the world of Formula One like never before"--